SISTEM INFORMASI PELAYANAN PASPOR REPUBLIK INDONESIA ONLINE PADA KANTOR IMIGRASI KELAS II - Ra Yadi (STIE 'INDONESIA' Pontianak, 2015)
The need for an information is the most important thing for everyone to take a decision. Internet is a medium that reaches the existence of all people in different places in the world, and people will compete to use it as a means of information and publications are inexpensive and fast. Online passport information service system is an application that is based on the thought that a good idea to access the fast service. Someone who needs a passport RI no longer need to waste a lot of time to come to the Immigration office to take care of it. They simply by using the internet to access pages and submit pre Immigration for a passport . In addition, the form of information about immigration can be known by the public